Age/Order of Acquisition influences at early stages of visual word processing: Evidence from homophonic formal priming in Spanish and English - Pérez-Sánchez, Miguel Á.; Marín, Javier; Izura, Cristina (Anales de Psicología / Annals of Psychology, 2024)
Words learned first or earlier in life are processed faster, with more accuracy, and are more resistant to brain injury than words learned some time later. This phenomenon is called the age-of-acquisition (AoA) effect. Current accounts of the AoA effect place its influence in the semantic system (i.e., the semantic hypothesis), or in the irregular connections formed between representations (i.e., the arbitrary mapping hypothesis). In this study, we tested the predictions derived from these hypotheses on visual word recognition using a formal masked priming paradigm with short SOA (43 ms) and two lexical decision tasks: one in Spanish and one in English. The AoA of the target words and the orthographic and phonological relationship between primes and targets were manipulated. Results from LMM analyses showed the main effects of AoA and phonological priming and an interaction where phonological priming affected only the recognition of late-acquired words. Neither the semantic nor the arbitrary mapping hypotheses fully explain these findings. Alternative accounts such as the phonological completeness or the sensorimotor hypotheses are discussed.